Neural basis of induced phantom limb pain relief. Issue 1 (7th January 2019) - Kikkert, Sanne; Mezue, Melvin; O'Shea, Jacinta; Henderson Slater, David; Johansen‐Berg, Heidi; Tracey, Irene; Makin, Tamar R.
Abstract : Objective: Phantom limb pain (PLP) is notoriously difficult to treat, partly due to an incomplete understanding of PLP‐related disease mechanisms. Noninvasive brain stimulation (NIBS) is used to modulate plasticity in various neuropathological diseases, including chronic pain. Although NIBS can alleviate neuropathic pain (including PLP), both disease and treatment mechanisms remain tenuous. Insight into the mechanisms underlying both PLP and NIBS‐induced PLP relief is needed for future implementation of such treatment and generalization to related conditions. Methods: We used a within‐participants, double‐blind, and sham‐controlled design to alleviate PLP via task‐concurrent NIBS over the primary sensorimotor missing hand cortex (S1/M1). To specifically influence missing hand signal processing, amputees performed phantom hand movements during anodal transcranial direct current stimulation. Brain activity was monitored using neuroimaging during and after NIBS. PLP ratings were obtained throughout the week after stimulation. Results: A single session of intervention NIBS significantly relieved PLP, with effects lasting at least 1 week. PLP relief associated with reduced activity in the S1/M1 missing hand cortex after stimulation. Critically, PLP relief and reduced S1/M1 activity correlated with preceding activity changes during stimulation in the mid‐ and posterior insula and secondary somatosensory cortex (S2). Interpretation: The observed correlation between PLP relief and decreased S1/M1 activity confirms our previous findings linking PLP with increased S1/M1 activity. Our results further highlight the driving role of the mid‐ and posterior insula, as well as S2, in modulating PLP. Lastly, our novel PLP intervention using task‐concurrent NIBS opens new avenues for developing treatment for PLP and related pain conditions.ANN NEUROL 2019;85:59–73.